Pengaruh Service Quality, Price, Dan Service Recovery Terhadap Customer Satisfaction (Studi Kasus Pada Konsumen di Roasting Kopi Mustika Dampit) - Muhamad Hendika Arifiano; Agus Widarko; Muhammad Ridwan Basalamah (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis research was conducted at Mustika Dampit Coffee Roasting. The type of research used in this research is quantitative research. The purpose of this study was to determine and analyze the effect of Service Quality, Price, and Service Recovery on Customer Satisfaction. The independent variables used are Service Quality, Price, and Service Recovery, while the dependent variable is Customer Satisfaction. The sample used in this study were 74 respondents who used roasting services for Mustika Dampit coffee roasting. Data collection techniques using a questionnaire. The analytical method used is validity test, reliability test, normality test, classical assumption test, hypothesis test, determination test with the help of SPSS software. The results of the study indicate that the Service Quality, Price and Service Recovery variables have a significant effect on Customer Satisfaction Keywords: Service Quality, Price, Service Recovery, Customer Satisfaction.